Islamic Religious Education And Multiculturalism - Apipudin Syarif (Yayasan Ilomata, 2021)
Indonesia as an archipelagic country has diversity. Be it ethnicity, culture, customs, race, religion or belief. The diversity of the Indonesian nation shows that society is colored with various kinds of differences. This condition has the potential for conflict among the community regarding religious diversity. is a very sensitive issue and can quickly lead to conflict within the community. Therefore, this article was written to offer the concept of Islamic religious education in the nuances of multiculturalism. And provide solutions and enlightenment towards a significant change in Islamic religious education in its various aspects, so that Islamic religious education becomes an inclusive and dynamic education and provides benefits for the development and progress of the nation in diversity.